2015
DOI: 10.3390/agriculture5030668
|View full text |Cite
|
Sign up to set email alerts
|

Biochars Derived from Gasified Feedstocks Increase the Growth and Improve Nutrient Acquisition of Triticum aestivum (L.) Grown in Agricultural Alfisols

Abstract: Abstract:Biochars are produced by low-oxygen gasification or pyrolysis of organic waste products, and can be co-produced with energy, achieving waste diversion and delivering a soil amendment that can improve agricultural yields. Although many studies have reported the agronomic benefits of biochars produced from pyrolysis, few have interrogated the ability of gasified biochars to improve crop productivity. An earlier study described the ability of a biochar that was derived from gasified Kentucky bluegrass (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…All treatments were replicated five times and randomly distributed on the greenhouse bench in Corvallis, OR, as previously described by Trippe et al (2015b). Day and night temperatures were 18 and 15°C, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All treatments were replicated five times and randomly distributed on the greenhouse bench in Corvallis, OR, as previously described by Trippe et al (2015b). Day and night temperatures were 18 and 15°C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that two gasified biochars produced from Kentucky bluegrass seed screenings (KB) or mixed conifer wood logging residues (CW) have properties making them suitable for agricultural soil amendments, including high cation exchange capacity (CEC), very low concentrations of potentially toxic compounds, and the ability to raise soil pH (Griffith et al, 2013; Trippe et al, 2015a, 2015b). The observed liming qualities of these biochars, combined with reports of heavy metal sorption by many types of biochars (Beesley et al, 2011; Tang et al, 2013; Zhang et al, 2013), led us to predict that they can facilitate the remediation of acid mine soil to a state that enables plant establishment.…”
mentioning
confidence: 99%
“…Apart from pyrolysis, heat treatment done on biomass for producing carbon is called torrefaction. The pyrolysis of biomass is a thermo-chemical process, which primarily refers to the decomposition of lignocellulose materials, other organic polymers, and biomass minerals [5][6][7]. The products of decomposition are created at a temperature between 400 • C and 800 • C with no oxygen.…”
Section: Introductionmentioning
confidence: 99%